Perlindungan Hukum Bagi Konsumen Terhadap Praktik Toeslag Jelang Hari Raya Oleh Perusahaan Otobus - Andri Maulana Adenin Lubis; Andryan Andryan (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
"Consumer Protection is all efforts that ensure legal certainty to provide protection to consumers," states Article 1 Point 1 of the Consumer Protection Law. The legal protection that consumers receive in their attempts to meet their needs from items that affect them directly is referred to as consumer protection. The term "consumer protection" refers to a wide range of topics, including the safeguarding of goods and services from the various stages of their acquisition to the end uses. "Consumer Protection is all efforts that ensure legal certainty to provide protection to consumers," states Article 1 Point 1 of the Consumer Protection Law. The legal protection that consumers receive in their attempts to meet their needs from items that affect them directly is referred to as consumer protection. The purpose of this study is to determine whether legal safeguards are available to consumers against the practice of extra charges (Toeslag) used by the bus company in the run-up to the holidays.